PENGEMBANGAN MEDIA CD INTERAKTIF MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP - Maharani, Hevy Risqi; Basir, M Abdul (Universitas Muria Kudus, 2016)
This research is a development that aims to develop mathematical learning media in the form ofan interactive CD. Interactive CD is supporting learning to improve problem solving ability juniorhigh school students. Development of interactive CD using 4D model was modified. Results of theexpert validation assessment showed interactive CD on the very good category with an averagescore of 4.23 out of a maximum range 5. Test the practicality of interactive CD shown by thepositive responses from teachers and students. Results showed that the effectiveness of interactiveCD has effective in improving problem solving abilities. This was demonstrated by the averageproblem solving ability of students that used interactive CD has achieved mastery of individualand classical. In addition, the average problem solving ability of students to use interactive CDwas better that not using interactive CD.